Carers' experiences of involuntary admission under mental health legislation: systematic review and qualitative meta-synthesis. Issue 2 (March 2020) - Stuart, Ruth; Akther, Syeda Ferhana; Machin, Karen; Persaud, Karen; Simpson, Alan; Johnson, Sonia; Oram, Sian
Abstract : Background: Carers are key providers of care and support to mental health patients and mental health policies consistently mandate carer involvement. Understanding carers' experiences of and views about assessment for involuntary admission and subsequent detention is crucial to efforts to improve policy and practice. Aims: We aimed to synthesise qualitative evidence of carers' experiences of the assessment and detention of their family and friends under mental health legislation. Method: We searched five bibliographic databases, reference lists and citations. Studies were included if they collected data using qualitative methods and the patients were aged 18 or older; reported on carer experiences of assessment or detention under mental health legislation anywhere in the world; and were published in peer-reviewed journals. We used meta-synthesis. Results: The review included 23 papers. Themes were consistent across time and setting and related to the emotional impact of detention; the availability of support for carers; the extent to which carers felt involved in decision-making; relationships with patients and staff during detention; and the quality of care provided to patients. Carers often described conflicting feelings of relief coupled with distress and anxiety about how the patient might cope and respond. Carers also spoke about the need for timely and accessible information, supportive and trusting relationships with mental health professionals, and of involvement as partners in care. Conclusions: Research is needed to explore whether and how health service and other interventions can improve the involvement and support of carers prior to, during and after the detention of family members and friends.